Fortalecimiento de la competencia intercultural en contextos educativos a través de la implementación de la Cátedra de Estudios Afrocolombianos CEA: una experiencia con algunos docentes de Bogotá (2021)
Although the Ministry of Education proposes the implementation of the CEA Afro-Colombian Studies Chair, currently some teachers of basic primary and secondary education from different areas of knowledge and from official schools and District of Bogotá in localities number 11 of Suba and locality 7 of Bosa do not have the guidelines or guidelines to address intercultural competence and / or develop pedagogical projects on the culture of communities. Afro-Colombian. Therefore, it is imperative to make these circumstances visible to mitigate the practices of racial and cultural discrimination in the school system, as an integral and transversal part of training processes